2016
DOI: 10.3390/app6120418
|View full text |Cite
|
Sign up to set email alerts
|

BSNCare+: A Robust IoT-Oriented Healthcare System with Non-Repudiation Transactions

Abstract: Abstract:Recently, the rapid advancement in technologies of modern intelligent objects has led to a new network paradigm, called the Internet of Things (IoT), in which every networked and automated object has been connected in a pervasive manner. New types of IoT-based application services are thus presented. In a healthcare oriented environment, the usage of IoT has brought opportunities for assisting physicians (or nurses) to provide on-demand and real-time body-care services to patients with higher accuracy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Non-repudiation: This metric encompasses the ability of the system to validate the presence or absence of an activity (Mosenia & Jha 2016;Yeh 2016). It ensures that the sending node is granted a delivery receipt and the receiver node is granted a proof on the identity of the sender so that none of them is denied in the process (Newaz et al 2020).…”
Section: B Security and Privacy In The Iomtmentioning
confidence: 99%
“…Non-repudiation: This metric encompasses the ability of the system to validate the presence or absence of an activity (Mosenia & Jha 2016;Yeh 2016). It ensures that the sending node is granted a delivery receipt and the receiver node is granted a proof on the identity of the sender so that none of them is denied in the process (Newaz et al 2020).…”
Section: B Security and Privacy In The Iomtmentioning
confidence: 99%
“…Previous studies identified significant advantages to utilizing Raspberry Pi for similar scenarios, including secure and robust healthcare services [62], intelligent video surveillance platforms [63], building management systems [64], and beehive monitoring [65]. Edge computing benefits have been clarified by several studies to include reduced response time [66] and energy consumption [67].…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…BSNCare+ was proposed in [ 36 ], it is an IoT-based health care system which implements BSN. Another application was proposed in [ 37 ], it name is BSN-Care.…”
Section: Revised Soa Applicationsmentioning
confidence: 99%
“…On the other hand, in the case of the implementations exposed in [ 34 , 35 ], security was left in the hands of the HTTPS protocol. Yeh et al [ 36 ] implemented a robust authentication system generating a random number and an exclusive function. The security in [ 37 ] is divided into two aspects: network security and data security.…”
Section: Analysis From the Perspective Of Security Implementationsmentioning
confidence: 99%